Factors Related to Pain in Patient with Knee Osteoarthritis - Sinwisarn, Narumon; Palanupat, Thippawan; Yokseng, Jaruwan (Journal of The Royal Thai Army Nurses, 2024)
This research is a retrospective study examining factors related to pain in patients with knee osteoarthritis at the outpatient clinic of Thasala Hospital between January 2020 and December 2022. Adults and older individuals, totaling 319 participants, were recruited for the study. Data was collected using personal information and self-care behavior record forms. The overall reliability for the entire set (r) was equal to .96. Data were analyzed using descriptive statistics, Chi-square relationship analysis, and binary logistic regression analysis. The results indicated that significant factors related to pain in patients with knee osteoarthritis include age, occupation, and self-manipulation of the knee. Factors predicting the risk of knee pain and other symptoms included joint stiffness, unsteady walking, swollen knees, and knee pain radiating to the leg or under the calf, as well as age and occupation. (P<.05) Based on the findings of this study, it is recommended that self-care education initiatives be enhanced, detrimental behaviors be modified. These interventions aim to decelerate disease progression, promote overall health, and preserve the occupational capabilities of patients with knee osteoarthritis.